PENGARUH SEFT (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN PENDERITA HIPERTENSI DI PUSKESMAS KAPASSA MAKASSAR - Zaenal; Rini Mustamin (Stikes Graha Edukasi Makassar, 2022)
Objective: This study aims to determine the effect of SEFT therapy on reducing blood pressure in patients with hypertension. Research design: The research design used by the researcher is an experimental design with a pre-post test with a control group with a sampling technique. The population in this study were all patients with hypertension, totaling 28 people in the Kapassa Health Center Makassar. The sample size in this study was 28 respondents. Collecting data using observation sheets and checklists. Research Results: The results of the analysis using Paired t-test in the intervention group showed the p-value of systolic and diastolic blood pressure was 0.000 (p-value <0.05). Conclusion: It can be concluded that there is an effect of SEFT therapy on reducing blood pressure in patients with hypertension. Suggestion: For patients with hypertension that SEFT (Spirtual Emotional Freedom Technique) therapy can be used as a drug companion therapy in treating hypertension with the help of SEFT nurses